Replacement of Enterococcus faecalis by Enterococcus faecium as the predominant enterococcus in UK bacteraemias. Issue 4 (10th December 2021) - Horner, Carolyne; Mushtaq, Shazad; Allen, Michael; Hope, Russell; Gerver, Sarah; Longshaw, Christopher; Reynolds, Rosy; Woodford, Neil; Livermore, David M
Abstract: Objectives: To review temporal changes in the proportions of different Enterococcus species recorded in two UK bacteraemia surveillance systems. Antibiotic resistance trends were also considered. Methods: We reviewed data for enterococci from 2001 to 2019 in: (a) the BSAC Resistance Surveillance Programme, which collected up to 7–10 bloodstream enterococci every year from each of 23–39 hospitals in the UK and Ireland and tested these centrally; and (b) PHE bacteraemia surveillance, using routine results from NHS microbiology laboratories in England. Results: BSAC surveillance, based upon 206–255 enterococci each year (4486 in total), indicated that the proportion of Enterococcus faecium rose from 31% (212/692) in the period 2001–3 to 51% (354/696) in the period 2017–19, balanced by corresponding falls in the proportion of Enterococcus faecalis . PHE surveillance provided a larger dataset, with >5000 enterococcus reports per year; although its identifications are less precise, it too indicated a rise in the proportion of E. faecium . BSAC surveillance for E. faecium indicated no consistent trends in resistance to ampicillin (≥86% in all years), vancomycin (annual rates 19%–40%) or high-level resistance to gentamicin (31%–59%). Resistance to vancomycin remained <4% in E. faecalis in all years, whilst high-level resistance to gentamicin fell, perhaps partly reflecting the decline of two initially prevalent gentamicin- and ciprofloxacin-resistant clones. Conclusions: Both surveillance systems indicate a growing proportion of E. faecium in enterococcal bloodstream infections. This is important because fewer therapeutic options remain against this frequently multiresistant species than against E. faecalis .